The Intervention of the Labor Electronic Mail by the Employer. Interview with Dr. Juan Carlos Calderón Ríos - Alva Cruz, Josselyn Estefanía (2016)
The present interview revolves around electronic mal of employees as a work tool and his relationship with the right of privacy and secrecy of telecommunications. Thus, it attempts to figure out the nature of electronic mail and other technologies as work tools, making difference from this same technologies in a personal context.